Manganese complexes of curcumin and its derivatives: Evaluation for the radical scavenging ability and neuroprotective activity - Opa Vajragupta (2018)
In this study, three manganese complexes of curcumin (Cp) and related compounds, diacetylcurcumin (AcylCp) and ethylenediamine derivative (CpED), were synthesized and evaluated in vitro for antilipid peroxidation and superoxide dismutase activity. The manganese complexes exhibited a great capacity to protect brain lipids against peroxidation with IC50of 6.3-26.3 μM. All manganese complexes showed much greater SOD activity than their corresponding antioxidant ligands as well as trolox with IC50values of 8.9-29.9 μM. AcylCp and curcumin manganese complexes (AcylCpCpx and CpCpx) also gave the highest inhibitory activity to H2O2-induced cell damage (oxidative stress) at 0.1 μg/ml (< 0.2 μM) in NG108-15 cells, which were more potent than curcumin and related compounds. The neuropharmacological tests in mice supported the idea that the SOD mimicking complexes were able to penetrate to the brain as well as their role in the modulation of brain neurotransmitters under the aberrant conditions. The complexes significantly improved the learning and memory impairment induced by transient ischemic/reperfusion. AcylCpCpx, CpCpx, and CpEDCpx showed significant protection at 6.25, 25, and 50 mg/kg (i.p.), respectively, whereas manganese acetate and curcumin had no effect at doses of 50 mg/kg. In addition, treatment of AcylCpCpx and curcumin significantly attenuated MPTP-induced striatal dopamine depletion in mice, which was in accordance with the increase in the density of dopaminergic neurons when compared with MPTP-treated mice. These results support the important role of manganese in importing SOD activity and consequently, the enhancement of radical scavenging activity. AcylCpCpx and CpCpx seem to be the most promising neuroprotective agents for vascular dementia. © 2003 Elsevier Inc.